2005
DOI: 10.1152/ajpheart.00495.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PKC modulates blood-brain barrier endothelial cell permeability changes induced by hypoxia and posthypoxic reoxygenation

Abstract: -The blood-brain barrier (BBB) is a metabolic and physiological barrier important for maintaining brain homeostasis. The aim of this study was to determine the role of PKC activation in BBB paracellular permeability changes induced by hypoxia and posthypoxic reoxygenation using in vitro and in vivo BBB models. In rat brain microvessel endothelial cells (RMECs) exposed to hypoxia (1% O 2-99% N2; 24 h), a significant increase in total PKC activity was observed, and this was reduced by posthypoxic reoxygenation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 48 publications
(78 reference statements)
3
64
1
Order By: Relevance
“…We have shown increased expression and activation of nPKC-y and aPKC-z after Hx. Our biochemical results are in agreement with an earlier in vitro and in vivo study (Fleegal et al, 2005), which showed that Hx and HR increased total PKC activity through altered expression of specific PKC isozymes. In vivo, Hx induced a large increase in activity of cPKC-g, -bII, and nPKC-e, whereas nPKC-y and aPKC-z showed modest increases, although nPKC-y showed much greater levels of expression during HR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have shown increased expression and activation of nPKC-y and aPKC-z after Hx. Our biochemical results are in agreement with an earlier in vitro and in vivo study (Fleegal et al, 2005), which showed that Hx and HR increased total PKC activity through altered expression of specific PKC isozymes. In vivo, Hx induced a large increase in activity of cPKC-g, -bII, and nPKC-e, whereas nPKC-y and aPKC-z showed modest increases, although nPKC-y showed much greater levels of expression during HR.…”
Section: Discussionsupporting
confidence: 93%
“…There was also increased membrane expression of the 47.9-kDa occludin band, whereas the 51.5-kDa band showed little change. Chelerythrine chloride has been shown to attenuate Hx-induced paracellular permeability changes rat brain microvessel endothelial cell cultures (Fleegal et al, 2005). We believe this is the first in vivo demonstration that PKC isozyme inhibition attenuates Hx-induced increased vascular permeability and supports the earlier in vitro work.…”
Section: Discussionsupporting
confidence: 81%
“…After 48 hours hypoxia, an increase in the permeability of brain capillary endothelial cell monolayers was observed that was associated with rearrangements of F-actin filaments and decreased ATP levels (Plateel et al, 1995). Changes in blood-brain barrier permeability are associated with protein phosphorylations that are regulated by protein kinase C isotypes, tyrosine phosphatase, or kinase activity (Staddon et al, 1995;Tsukamoto and Nigam, 1999;Fleegal et al, 2005). It is likely that cytoskeletal reorganization has an important role in the relation between b 1 -integrin adhesion and tight junction integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In BBB endothelial cells treated with Ang II (100 nmol/L) for 0 to 6 h, there was a significant increase in PKC activity seen as early as 1 h, which remained elevated at both 2 and 6 h ( Figure 5). As studies have shown that PKC can regulate paracellular permeability and several studies have suggested that PKC regulates the TJs (Clarke et al, 2000;Fleegal et al, 2005;Wosik et al, 2007), we also looked at whether Ang II altered the expression of the TJ proteins occludin and claudin 5. There was no change in the expression of these two proteins or the cytoskeletal protein, actin ( Figure 6; Table 1).…”
Section: Angiotensin II Stimulates Protein Kinase C Activity In Cultumentioning
confidence: 99%